The 2013 elections in Nepal - Gellner, D (Routledge, 2014)
In spite of all the difficulties, the November 2013 elections in Nepal passed off for the most part peacefully and with fewer irregularities than ever before in Nepal. The electoral system was the same as the system used in 2008, with a combination of First Past the Post and Proportional Representation. The results were a defeat for the Maoists, who went from being the biggest single party to the third biggest party. The victors were the two older established parties, the Nepali Congress and the Unified Marxist-Leninists, who seem to have benefitted from the voters dissatisfaction with the Maoists’ showing in government. The second big losers in the election were the parties who favoured an ethnic-based solution to Nepal's problems, though the relationship between the Madheshis and the centre remains an unsolved problem.